2016
DOI: 10.1038/srep39557
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cytokeratin 19 head domain and HER2 in the cytoplasm leads to activation of HER2-Erk pathway

Abstract: HER2 is a receptor tyrosine kinase and its upregulation via activating mutations or amplification has been identified in some malignant tumors, including lung cancers. Because HER2 can be a therapeutic target in HER2-driven malignancies, it is important to understand the molecular mechanisms of HER2 activation. In the current study, we identified that cytokeratin 19 (KRT19) binds to HER2 at the inside face of plasma membrane. HER2 and KRT19, which were concurrently introduced to a human embryonic kidney 293 T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…As KRT19 expressed in various cancer types [ 36 , 37 , 38 , 39 , 40 , 41 , 44 , 45 , 46 , 47 ], we checked the expression level of KRT19 in five paired breast cancer tissue and adjacent normal breast tissues using reverse transcriptase-polymerase chain reaction (RT-PCR) analysis. However, our RT-PCR results showed that the expression of KRT19 was attenuated in breast cancer tissue (C) when compared to their normal (N) counterparts ( Figure 1 A, upper panel); the clinical characterization of breast cancer patients was overviewed in Figure 1 A, lower panel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As KRT19 expressed in various cancer types [ 36 , 37 , 38 , 39 , 40 , 41 , 44 , 45 , 46 , 47 ], we checked the expression level of KRT19 in five paired breast cancer tissue and adjacent normal breast tissues using reverse transcriptase-polymerase chain reaction (RT-PCR) analysis. However, our RT-PCR results showed that the expression of KRT19 was attenuated in breast cancer tissue (C) when compared to their normal (N) counterparts ( Figure 1 A, upper panel); the clinical characterization of breast cancer patients was overviewed in Figure 1 A, lower panel.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a recent study showed that HCC progression could be regulated through PDGFRα-laminin B1-keratin 19 cascade and this cascade could drive early recurrence, microvascular invasion, and metastasis in HCC [ 37 , 38 , 39 ]. Furthermore, it is demonstrated that KRT19 transcription could be increased through HER2/ERK/SP1 signaling pathway, in a consequence, KRT19 translocated to HER2 receptor then bound and stabilized the HER2 activation in breast and lung cancer [ 40 , 41 ]. In addition, KRT19 is normally expressed in the stem cell region of the hair follicle [ 42 , 43 ], and it is overexpressed in various radio-resistant solid tumors including colon and intestine progenitor/stem cells [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some keratins, such as K14, can promote cell migration, and their expression is correlated with both invasive carcinomas and migration during embryonic development (Sun et al, 2010 ; Cheung et al, 2013 , 2016 ). Still other keratins, like K19, seem to have multiple functionalities that may greatly depend on the expression levels and more nuanced roles in modification of signal transduction pathways (Ohtsuka et al, 2016 ; Saha et al, 2017 ). How then might intermediate filaments impact migration when they are doing more than simply resisting motility?…”
Section: Intermediate Filaments As Determinants Of Migrationmentioning
confidence: 99%
“…CK-19 also plays a key role in HCC with the expression of invasion-related/metastasis-related markers (VASP, LAMB1, PDGFRA), biliary marker (CD133, GSTP1, JAG1) and members of microRNA family 200, especially in PDGFRA-LAMININ B1-CK-19 cascade [ 29 , 30 ]. In lung cancer, CK-19 intracellularly binds to HER2 to promote HER2 activation [ 31 ]. Additionally, CK-19 is related to V600E in papillary thyroid carcinoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%